LITERASI REVIEW SISTEM DRAINASE PERMUKAAN UNIVERSITAS PANCASAKTI TEGAL - Soebyakto, Soebyakto; Yusuf, Muh.; Santoso, Teguh Haris; Salsabilla, Nadya Shafira; Hermawan, Okky Hendra; Susilorini, Retno (LPPM Institut Pendidikan Nusantara Global, 2024)
Surface drainage is the regular diversion or disposal of excess water from the land surface through improved natural channels or constructed water channels, if necessary, equipped with the formation and assessment of the land surface for these channels. Campus 1 of Pancasakti University Tegal is located in the coastal area of ​​Tegal City. In some cases, the land surface of Pancasakti Tegal University is shaped or graded to create a slope towards the channel. The different types of surface drainage systems are open channels, humps and depressions, embankments, and building edge drains. Drainage is the natural or artificial removal of surface and subsurface water from an area that has excess water. Internal drainage on most educational sites can prevent severe waterlogging, but many soils require artificial drainage to improve management of excess water. The first step in installing a drainage system is to survey the area and determine the type of system needed. During high tides and high rainfall, water intrusion occurs into the grounds of Pancasakti University Tegal. This involves assessing the amount of rainfall and sea tides in waterlogged areas, the slope of the land, and the type of soil. This will tell us what type and material of drainage system is best for the structure. The drainage problem that often arises is the lack of coordination and synchronization with other infrastructure development. In general, the handling of the drainage system is still partial, so it does not solve the problem of flooding and inundation completely. The purpose of this paper is to review several factors that cause water intrusion in drainage due to high tides causing water flow to be obstructed so that when it rains, water overflows and puddles occur.